SPOTTING FAKE NEWS AND HOAXES IN CRITICAL READING COURSE USING MEDIA LITERACY PROJECT - Komalasari, Adesti (LINGUISTIKA, 2018)
With the extremely easy access to information through online platform and the increasing numbers of internet users, people get abundant information both from valid and reliable sources and invalid and unreliable ones. Given the situation, the existence of hoaxes and fake news is inevitable and one of the methods to tackle the spreading of fake news is by increasing students' literacy level, especially in recognizing news validity and reliability. In order to increase one's literacy level, some extensive hours of reading are required so that they are exposed to news and later become quality news literate. Media Literacy Project becomes a strategy to introduce the characteristics of hoaxes and fake news and this strategy is implemented in Critical Reading course, whose objectives are to distinguish facts from opinions, draw conclusions from written material based on knowledge, experience, logic and awareness of the source validity and reliability, and develop and practice critical reading skills necessary for success in content area courses by interpreting, evaluating, and applying the knowledge to understanding the reading content and context. This research tries to examine the significance of readers' literacy level in recognizing information validity and reliability and to analyze how Media Literacy Project could increase students' literacy level and their awareness of fake news and hoaxes written by some news portals